Different effect of cadence on cycling efficiency between young and older cyclists - Sacchetti, M.; Lenti, M.; Di Palumbo, A. S.; de Vito, G. (Medicine & Science in Sports & Exercise, 2010)
Purpose: We investigated the difference in the cadence-efficiency relationship between young and older competitive cyclists.